Berbantuan Alat Peraga Papan Garis Bilangan Terhadap Kemampuan Pemecahan Masalah pada Materi Operasi Hitung Bilangan Bulat Kelas VII SMP Negeri 8 Satap Simpang Hulu - Monika Rita; Muhamad Firdaus; Wandra Irvandi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Students' problem-solving ability on integer arithmetic operations is still relatively low, one of the causes is the uniform learning and lack of attention to the differences in students' learning needs. This study aims to determine the effect of differentiated learning assisted by a number line board on the problem-solving ability of seventh-grade students on integer arithmetic operations at SMP Negeri 08 Satap Simpang Hulu. The study used a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The research sample consisted of two classes, namely the experimental class and the control class. Data were collected through essay tests compiled based on Polya's problem-solving indicators. Data analysis was carried out through analysis prerequisite tests, independent t-tests, and effect size calculations. The results showed a significant difference between the problem-solving abilities of students in the experimental class and the control class with a significance value of 0.001 (<0.05). The average posttest score of the experimental class was higher than that of the control class. In addition, the effect size value of 0.915 indicated a large influence. These findings confirm that differentiated learning assisted by a number line board is effective and practically meaningful in improving students' problem-solving abilities.